Bibliometric analysis of swimming learning models for students (2002-2024): Trends, gaps, and future directions - Arhesa, Sandra; Ma'mun, Amung; Lumba, Andreas J. F.; Blegur, Jusuf; Calunsag, Buena D. (Jurnal Keolahragaan, 2025)
Drowning during swimming has become a significant public health concern that urged the World Health Organization to call for all school-aged children to be taught basic swimming skills, water safety, and rescue techniques. In this teaching, efficiency shall be obtained with the help of an effective learning model. This study will investigate the publication trends of research about swimming learning models carried out for students during the last 22 years, from 2002 until 2024, using the data from the Scopus database. The search was carried out on August 7, 2024, by title, abstract, and keywords, using the sets of words "swimming AND learning AND model AND for AND students," and obtained 47 documents, where 66% were articles, 12.8% conference reviews, 10.6% conference papers, 4.3% book chapters, 2.1% books, 2.1% notes, and 2.1% reviews. The most frequent year of publication corresponded to the year 2023, with a total of 10 documents. Three each by the International Journal of Human Movement and Sport Science and Emerald Emerging Markets Case Studies. Among the 15 contributing authors, only two documents were contributed by Firmansyah Dlis and Mao Jie. Affiliation-wise, two were contributed by Universitas Negeri Yogyakarta, Wuhan Sports University, Universitas Negeri Surabaya, and Universitas Negeri Jakarta. Nationally, China tops the list with eight documents. The most cited article, by Iserbyt et al. (2016), received 44 citations in 22 years. Based on the VOSviewer analysis, the "swimming learning model" item count is low (47 documents in 22 years). Thus, the visualization has been limited, with only a few networking-connected words. Such a scenario represents that research on swimming learning models for students still holds potential for further investigation.